2012
DOI: 10.1038/ncomms2315
|View full text |Cite
|
Sign up to set email alerts
|

Probing the catalytic activity of porous graphene oxide and the origin of this behaviour

Abstract: Graphene oxide, a two-dimensional aromatic scaffold decorated by oxygen-containing functional groups, possesses rich chemical properties and may present a green alternative to precious metal catalysts. Graphene oxide-based carbocatalysis has recently been demonstrated for aerobic oxidative reactions. However, its widespread application is hindered by the need for high catalyst loadings. Here we report a simple chemical treatment that can create and enlarge the defects in graphene oxide and impart on it enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
520
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 575 publications
(549 citation statements)
references
References 46 publications
19
520
0
10
Order By: Relevance
“…25 In this work, however, reduced GO (rGO) was used due to its better catalytic profile for various organic transformations against the GObased catalyst. 26 Notably, the use of rGO as a catalyst has not been reported for an efficient etherification of HMF under mild conditions. For facile immobilization of the rGO by external magnet force, magnetic Fe 3 O 4 nanoparticles were loaded on the rGO prepared by Hummer's method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…25 In this work, however, reduced GO (rGO) was used due to its better catalytic profile for various organic transformations against the GObased catalyst. 26 Notably, the use of rGO as a catalyst has not been reported for an efficient etherification of HMF under mild conditions. For facile immobilization of the rGO by external magnet force, magnetic Fe 3 O 4 nanoparticles were loaded on the rGO prepared by Hummer's method.…”
Section: Resultsmentioning
confidence: 99%
“…For facile immobilization of the rGO by external magnet force, magnetic Fe 3 O 4 nanoparticles were loaded on the rGO prepared by Hummer's method. 26 After the immobilization of the Fe 3 O 4 /rGO mixture catalyst inside the wall of PTFE (500-μm id, 1.6-mm od, 200-cm length and 120-μl volume), the commercial HMF and ethanol were introduced from the horizontal inlet and vertical inlet of the T-junction, respectively, into the PTFE capillary to optimize the conversion to EMF by varying the reaction conditions (50-100°C, 6-18 min, see ESI, Supplementary Figure S1). At 100°C, unstable microfluidic flow was observed, which was presumably due to the low boiling point of ethanol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we briefly review the ESR investigations reported [10][11][12][13] in the literature while probing for the spin properties of graphene-derived materials. For instance, an interesting work 10 carried out on chemically-derived graphene oxide and reduced graphene oxide through ESR spectroscopy reported on the presence of localized paramagnetic defects and discussed how these defects influence the transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…This study has identified both localized and extended defects from the ribbons. In another systematic work, 12 Su and co-authors have employed ESR spectroscopy in exploring the catalytic properties of graphene oxide and illustrated the role of defects, concluded that localized spins are created at the edge of pi-electron system. In another work, 13 while exploring the spin magnetism of nano sized graphite particles, EPR spectroscopy has revealed the presence of strongly coupled localized and itinerant spins.…”
Section: Introductionmentioning
confidence: 99%